Descentralização do processo de licenciamento ambiental - CHAVES, Eduardo Melo (2024)
This paper aims to debate and demonstrate the need to use the decentralization of the licensing process provided for in COEMA resolution no. 162/2021, as a way of streamlining and making projects viable and achieving a reduction in the time and cost of licensing works and services. Data on the time required to obtain an Installation License (LI) at the state level (using the state of Pará as a reference) are compared to the municipal level (using the Municipality of Belém as a reference). The differences between the time to obtain the Installation License between the state and municipal levels are discussed and presented, obtaining a difference between the state and municipal levels between the average time and the maximum time of 430 days (1 year and 2 months) and 1141 days (3 years and 2 months) respectively